1)t+2,5t-1=0,5t+2;
3t=3
t=1
2)1,3v+18=2v-16+v;
-1,7v=-34
v=20
3)x+0,2x-8=8-0,4x
1,6x=16
x=10
1. t+2,5t-1=0,5t+2
3,5t-1=0,5t+2
3,5t-0,5t=2+1
2. 1,3v+18=2v-16+v
1,3v+18=3v-16
1,3v-3v=-16-18
3. x+0,2x-8=8-0,4x
1,2x-8=8-0,4x
1,2x+0,4x=8+8
1)t+2,5t-1=0,5t+2;
3t=3
t=1
2)1,3v+18=2v-16+v;
-1,7v=-34
v=20
3)x+0,2x-8=8-0,4x
1,6x=16
x=10
1. t+2,5t-1=0,5t+2
3,5t-1=0,5t+2
3,5t-0,5t=2+1
3t=3
t=1
2. 1,3v+18=2v-16+v
1,3v+18=3v-16
1,3v-3v=-16-18
-1,7v=-34
v=20
3. x+0,2x-8=8-0,4x
1,2x-8=8-0,4x
1,2x+0,4x=8+8
1,6x=16
x=10